CONSUMER PURCHASING BEHAVIOUR AND MEAT CONSUMPTION PATTERNS IN TAMIL NADU - P. Sivakumar; P. Vignesh; R. Kiruba (Indian Journal of Veterinary and Animal Sciences Research, 2026)
This study investigates the factors influencing meat purchasing behavior among consumers across different districts in Tamil Nadu. Using data collected through Google Forms, the research highlights variations in meat consumption, expenditure, packaging preferences, and awareness of online meat delivery platforms, along with demographic characteristics, purchasing habits, and preferences regarding meat products. The findings emphasize the influence of socio-economic factors, awarenessof processed meats, hygiene concerns, and online purchasing behavior in shaping consumer decisions. Significant differences were observed across districts, primarily driven by variation in urbanization, income levels, and awareness of hygiene standards. The results revealed that chicken was the most preferred meat (58.5%) followed by seafood (19.4%) and chevon (7.2%). The frequency of meat consumption in Tamil Nadu indicated that once a week (37.5%) followed by twice a week (29.4%). A majority of respondents (73.5%) were aware about processed meat. Additionally, 64% preferred consuming meat in gravy form. 61.8% of consumers expressed their reason for meat purchase based on quality and followed by price (11.8%). Overall, the study concludes that improving hygiene standards, ensuring certified meat products, and promoting hygienic packaging and food safety awareness- while leveraging the rise of online meat purchasing can better address evolving consumer expectations across urban and rural markets in Tamil Nadu.